Case report: First report of potentially zoonotic Gongylonema pulchrum in a free-living roe deer (Capreolus capreolus) in Slovenia - Bandelj, Petra; Žele Vengušt, Diana; Vengušt, Gorazd; Kušar, Darja (Frontiers in Veterinary Science, 2024)
Adult female and male Gongylonema nematodes were found in the oesophagus of a free-living roe deer (Capreolus capreolus) in Slovenia during passive health surveillance of wildlife. The genus Gongylonema was determined by light microscopy based on the genus-specific cuticular bosses in the anterior part of the parasite. Molecular methods were used to confirm the species Gongylonema pulchrum, which has zoonotic potential. Although Gongylonema species are considered common and distributed worldwide, this is the first report of G. pulchrum in an animal on the territory of Slovenia and the first molecular report in a roe deer worldwide. The parasite is likely to be underdiagnosed, misdiagnosed or goes unnoticed as the animals show little or no clinical signs and minor pathological lesions. Slaughterhouse workers, hunters and veterinarians should be aware of this elusive parasite. Examination and evisceration of the upper digestive tract of animals should therefore be carried out more carefully.